Simplify −34r + 3 − 56r − 6

.(1 point)

1 answer

To simplify the expression \(-34r + 3 - 56r - 6\), we can combine like terms.

First, combine the \(r\) terms: \[ -34r - 56r = -90r \]

Next, combine the constant terms: \[ 3 - 6 = -3 \]

Putting it all together, the simplified expression is: \[ -90r - 3 \]

So, the final answer is: \[ \boxed{-90r - 3} \]

Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions